The contribution of corporate responsibility in the manufacturing industry of Bogotá, Colombia. (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2021)
Through this research, the perception of medium and large manufacturing companies in Bogotá regarding the contribution of corporate social responsibility (CSR) programs to sales, brand image, positioning, sense of belonging, and exports was explored. This was a qualitative study, considering the level of depth and the target audience (those responsible for CSR programs in the companies). Nine in-depth interviews supported by projective techniques with a structured guide were conducted. The research revealed that CSR programs in medium and large manufacturing industries in Bogotá contribute to brand image and positioning, as well as to generating a greater sense of belonging among employees. The role of CSR in exports was also highlighted, considering that this is an important factor for both companies and consumers globally. It opens doors and represents a competitive advantage that companies consider when forming partnerships with foreign companies.
Keywords: Environment; Environmental attitude; Responsible Consumption